We Are Coming Home: Repatriation and the Restoration of Blackfoot Cultural Confidence - Edited by Gerald T. Conaty (Athabasca University Press, 2015)
In 1990, Gerald Conaty was hired as senior curator of ethnology at the Glenbow Museum, with the particular mandate of improving the museum's relationship with Aboriginal communities. That same year, the Glenbow had taken its first tentative steps toward repatriation by returning sacred objects to First Nations' peoples. These efforts drew harsh criticism from members of the provincial government. Was it not the museum's primary legal, ethical, and fiduciary responsibility to ensure the physical preservation of its collections? Would the return of a sacred bundle to ceremonial use not alter and diminish its historical worth and its value to the larger society? Undaunted by such criticism, Conaty oversaw the return of more than fifty medicine bundles to Blackfoot and Cree communities between the years of 1990 and 2000, at which time the First Nations Sacred Ceremonial Objects Repatriation Act (FNSCORA)-still the only repatriation legislation in Canada-was passed. "Repatriation," he wrote, "is a vital component in the creation of an equitable, diverse, and respectful society." We Are Coming Home is the story of the highly complex process of repatriation as described by those intimately involved in the work, notably the Piikani, Siksika, and Kainai elders who provided essential oversight and guidance. We also hear from the Glenbow Museum's president and CEO at the time and from an archaeologist then employed at the Provincial Museum of Alberta who provides an insider's view of the drafting of FNSCORA. These accounts are framed by Conaty's reflections on the impact of museums on First Nations, on the history and culture of the Niitsitapi, or Blackfoot, and on the path forward. With Conaty's passing in August of 2013, this book is also a tribute to his enduring relationships with the Blackfoot, to his rich and exemplary career, and to his commitment to innovation and mindful museum practice. "...deeply informative and readable.... An absence of Canadian texts in the museum field and in cultural communication leaves open the mistaken idea that we are mere ciphers for practices from abroad. By making an important Alberta story available in this fascinating and important volume, AU Press has performed an essential cultural service for all Canadians." -Literary Review of Canada